Acquired and hereditary forms of recurrent angioedema: Update of treatment - Bork, K. (Allergol Select, 2018)
The aim of treatment of hereditary angioedema (HAE) due to C1 esterase inhibitor deficiency (HAE-C1-INH) is either treating acute attacks or preventing attacks by using prophylactic treatment. For treating acute attacks, plasma-derived C1 inhibitor (C1-INH) concentrates, a bradykinin B2 receptor antagonist, and a recombinant human C1-INH are available in Europe. In the United States, a plasma-derived C1-INH concentrate, a bradykinin B2 receptor antagonist, and a plasma kallikrein inhibitor were approved for the treatment of acute attacks. Fresh frozen plasma is also available for treating acute attacks. Short-term prophylactic treatment focuses on C1-INH and attenuated androgens. Long-term prophylactic treatments include attenuated androgens such as danazol, stanozolol, and oxandrolone, antifibrinolytics, and a plasma-derived C1-INH concentrate. Plasma-derived C1-INH and a bradykinin B2 receptor antagonist are admitted for self-administration and home therapy. So the number of management options increased considerably within the last few years thus helping to diminish the burden of HAE.